Evolution of decentralization in Chile between 1990 and 2022. Actors, changes and perspectives about regional governance - Montecinos, Egon (Revista del CLAD Reforma y Democracia, 2023)
The first election of regional governors in 2021 concludes a set of pro-decentralization reforms, initiated at the beginning of 1990, which were expected to strengthen regional democracy. This article argues that this objective is unfinished, given that this set of reforms emphasized the administrative dimension of decentralization and was led by a centralist political elite, with incomplete political reforms and little involvement of territorial actors. As a result of the trajectory of the process, an elitist regional governance with a centralist institutional component predominates, with many difficulties for regional governments to fully exercise their role. Despite this trajectory, and given the current political context, the article concludes that in general there is a favorable future scenario for the strengthening of decentralization and the configuration of a regional governance that broadens participation and deepens democracy.